Interface crack behavior of thermal protection coating of gun bores under transient convective cooling. (July 2022) - Hou, Zongbin; Peng, Shengyang; Yu, Qingmin; Shao, Xiaojun
Highlight: Temperature-independent material parameters underestimate the driving force of interfacial crack propagation. Increasing crack density and coating thickness can reduce interfacial crack energy release rate. Shear mode dominates the fracture mode of interfacial cracks during convection cooling. Abstract: Electroplating chromium coating is a common and critical surface coating technology for the artillery bore. In this study, the fracture behavior of interface cracks in the chromium coating-steel substrate system under transient convective cooling was studied by the finite element method. A two-dimensional model containing periodic segmented coatings was established, and the temperature dependence of material parameters was considered. The effects of convection strength, crack geometry and coating thickness on the delamination behavior of chromium coatings were discussed. It was found that the increase in crack density and coating thickness reduced the energy release rate. The shear mode dominates the fracture mode of the interface crack during the convection cooling period, and the crack closes once the convection stops. When the crack density and coating thickness reach a certain value, the proportion of the shear traction no longer changes. These results can provide references for artillery coating design.